PROBLEMS OF GAS PRICING IN UKRAINE - Artamonova, Halyna (Journal of European Economy, 2017)
The question of economic feasibility of tariffs for energy, particularly natural gas, both imported and domestic is analyzed in the article. It is concluded that the population’s needs can be fully satisfied by Ukrainian gas, and prices of wholesale gas markets should be formed as a result of long-term contracts between producers and buyers. Special attention is focused on the inadmissibility of the use of any rent payments in the gas pricing in Ukraine. Priority measures to reform Ukraine’s gas sector, including reasonable use of energy saving technologies and adaptation of European experience of gas and heating pricing for the population, are determined.